Developing an ESP Guideline for Flight Attendant Students in a Chinese Vocational Undergraduate University - Zhou, Yan (none, 2025)
English for Specific Purposes (ESP) is vital in training flight attendants, particularly within China’s vocational undergraduate system. Yet a clear mismatch remains between airline English requirements and the ESP content taught in universities. This study adopted a convergent parallel mixed methods design to examine the English needs of flight attendant students by analyzing both present and target situations of language use. Data were collected from 186 students and six teachers through documentation analysis of the current ESP syllabus, questionnaires, interviews, and classroom observations. Results show that while students regard English as essential for career development and self-rate their proficiency as “moderate”, significant weaknesses persist across sub-skills. Speaking emerged as the most critical competence, followed by listening with grammar and vocabulary also requiring improvement. English certification was identified as a decisive factor in airline recruitment. Students further highlighted the value of interactive, learner-centered activities and AI-enhanced ESP. The study concludes that existing ESP provision does not fully align with industry demands and proposes a practical course design guideline to bridge this gap.